Identification of key assessment indicators of the zero waste management systems - Zaman, Atiq (Elsevier, 2014)
The concept of 'zero waste' management has emerged as an innovative way to tackle waste problems. A number of researchers have already defined the concept in different ways. Zero waste management is a holistic waste management concept that recognises waste as a resource which is produced at the intermediate phase of the resource consumption process. To measure the performance and progress in zero waste management, it is important to have certain indicators that sketch different waste management systems and predict effective development scenarios. A number of indicators on waste management systems have already been developed by many researchers in many cities and countries. The currently available indicators are not yet sufficiently integrated and identified as key indicators for assessing waste management systems. Therefore, in a significant number of waste management researches, dissimilar reporting, data representation and assessment indicators have been used without a proper comparative benchmark. This study is aimed to identify the core zero waste indicators which could be used to assess the performance of the zero waste management systems. A set of indicators have been identified by waste experts as the key indicators for the zero waste management systems. After an intensive literature review, the zero waste indicators were broadly categorised in seven different domains such as geo-administrative, socio-cultural, management, economic, environmental, organisational and policy. A total of 238 indicators were identified as preliminary zero waste indicators and sent to the number of 650 highly experienced waste professionals around the globe for their feedback. About 31 (n = 31) professionals participated (response rate 4.8%) in the online survey and rated the indicators from not needed to very high priority. About 165 indicators were rated as potential indicators for the assessment of zero waste management. As 165 indicators are still very comprehensive, for practical application, 56 indicators were identified as the most important indicators for zero waste management systems and were rated as nearly very high priority indicators by the waste experts.